Automatic assembly design project 1968/69: report of the control and motivation committee - Wrigglesworth, D.; LeHunte, G.; Kimber, A.; Gray, A. (College of Aeronautics)
Methods of control for automatic assembly machines are surveyed. The control requirements of the versatile automatic assembly machine are analysed, and the most practical system is specified and designed in detail.